Saberes que sabem à extensão - Oliveira, Irlane Maia de (2017)
The university extension has a significative meaning in my life, by its practices I learned to live the university, and this experience was based in a concern of how the university can dialogue with the community‘s knowledge recognition so they can bring back and amplify the content‘s repertory to be instructed under a context that can reflect the reality to their students. This experience also raised concerns of how the indissociability‘s practices are headed among teaching, researching and extension, once the extension‘s actions are disengaged from the course‘s politics projects and arrange themselves in mere punctual actions. With the contribution‘s perspective to the academic verticalization knowledge process becomes a dialogue process, it‘s necessary to reinterpret the university‘s relation with the community, and the community with the school. This reinterpretation cannot happen without hearing the community‘s knowledge, since without the hearsay the university social practices tend to keep their purely assistance spirit. Along with this perspective, the school is a key partner in the process and may also review its social practices, since this one not rarely devalue or ignore the community‘s knowledge. This assertive comes from the experience as state teacher in the years of 2000 to 2009. The research‘s base problematization is empiric and was molded by the extension‘s actions of Universidade Federal do Amazonas, where was possible to predict the it‘s social practice maintains the verticalization, and being productive and holder of knowledge, extending to community. Secured by Paulo Freire and the reflection about the alert made by one of the greatest historian of the present time, the english Eric Hobsbawn (1995), about our social past destruction, was possible to involve the elderly at the research, because it‘s understandable that youth people grows in an environment without any connection with their past generation experiences. Besides this, instigated by the sentence ―When an old man dies, it‘s like a library that burns‖, find its sense, meaning and structured elements to make ourpositionin relation of the following problem: How to transform primeval knowledge in school knowledge by the community‘s hearsay, in dialogue with academic‘s knowledge? The methodologic incursion approach qualitatively the Oral History data‘s as methodology and describe the university‘s extension as constructive dialogue that unveils the Amazon as sense unit, showing innovative actions to the 21st century university – essentially at colonized and multicultural countriesby a postcolonial perspective -, as it‘s social role can be restructured to break with the knowledge‘s verticalization if we want to improve, in fact, to a new and differentiated social practice which the auditory turns the dialogue in daily exercise with the community in partnership with the school.